MANAJEMEN INTEGRASI ILMU UMUM DAN ILMU AGAMA DALAM MEMBANGUN GENERASI QURANI DI MADRASAH TSANAWIYAH AL HIKAM - Muhammad Maulana Ridwan; Samdani Samdani; Agnur Frizkia Erlambang; Rahmat Kurniawan (STKIP Pesisir Selatan, 2025)
The purpose of this study is to analyze the management methods applied in combining the general and religious curricula at Madrasah Tsanawiyah (MTs) Al Hikam with the hope of achieving the vision of developing a Qur'anic Generation. The Qur'anic Generation is defined as students who not only excel in modern science and technology, but also have spiritual depth, good morals, and are able to apply the values of the Qur'an and Hadith in their daily lives. This study used a qualitative method with a case study at MTs Al Hikam, involving in-depth interviews with the head of the madrasah, teachers, and direct observation of the teaching and learning process. The findings of this study reveal that integration is carried out through three main aspects: (1) Curriculum Integration (thematic syllabus that links general material with religion), (2) Learning Integration (integrated tahfiz method and contextual teaching), and (3) Cultural Integration (daily worship habits and role models from teachers). The role of the madrasah principal as a transformational leader is crucial to maintaining the continuity and consistency of this integration program. Effective implementation of this integration management has been proven to have a positive impact on students' academic and spiritual competency achievements.